Peran Pengorganisasian Komunitas Pager Asik terhadap Permasalahan Sosial di Kota Tasikmalaya - Adzani, Alifa Maula; Aulia, Gita; Sulistiani; Holfinur, Zamzam (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Abstract. Social problems are indeed problems that are not resolved in the community, ranging from poverty, illiteracy, malnutrition, unemployment, theft, restraint of children and women and other more complex problems. This research was conducted with the aim of describing the organization of the Asik Pager Community towards social problems in the City of Tasikmalaya. The method used is a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews and documentation. Based on the results of the study, that there are several substantial matters concerning the role of the pager asik community organizing in overcoming social problems in the City of Tasikmalaya, namely social empowerment/organization, social advocacy, and fulfillment of basic needs/social assistance. Program implementation carried out by Pager Asik is divided into three scales, namely micro scale or with little coverage, where micro scale programs are carried out against individual targets, so the target is not more than two people.